Effective Factors on Voluntary Choice of an Auditor - Yahya Hassas Yeganeh; Rasool Heidari (مطالعات تجربی حسابداری مالی, 2008)
According to Agency Theory, when size, debt leverage and salaries of personals is increased, the probability of voluntary choice of qualified auditor will be increased. Therefore, we selected 342 listed companies in Tehran Stock Exchange (TSE). We examined a selection of qualified auditors when the variable is changed. The result of this research shows no relation between debt and salaries, and selection of qualified auditors. We   used De. Angelo (1981) modified Auditing qualified index for the selection of auditors.